Formation of Regional Public Organizations in Last Quarter of XIX — Early XX Century (Tomsk Province) - A. V. Filimonov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The activity of officials on the formation of public non-political organizations of the Tomsk province in the last quarter of the XIX — early XX centuries is considered. The picture of the current state of research of public organizations and officials of the Russian Empire is presented. Based on the analysis of a number of published and unpublished sources, examples of the participation of representatives of the Tomsk administration in the process of creating various societies are revealed. The features of interaction of officials with representatives of the local society (scientists, political exiles, merchants, industrialists), as well as with city government bodies are highlighted. The main forms of the contribution of the Tomsk bureaucracy to the creation of societies are determined: the development of a charter, a petition to the state to open an organization, a search for like-minded people, and financial support. The author establishes the main reasons for the participation of employees of administrative institutions of the Tomsk province in the formation of new societies: job responsibilities, joint initiative with members of the public, personal interest. A correlation was found between the direction of work of some organizations and the official and non-official activities of civil servants. In general, the potential for establishing interaction between officials and the local community in the process of creating non-political organizations was noted.